2007 International Aegean Conference on Electrical Machines and Power Electronics 2007
DOI: 10.1109/acemp.2007.4510594
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of current harmonics in induction motors with Artificial Neural Network

Abstract: In this paper, Artificial Neural Network (ANN) technique has been used for the estimation of voltage THD (Total Harmonic Distortion), and current THD, mainly from input and output measurements of five different chorded induction motors fed from a pulse width modulation inverter voltage supply. A sinusoidal pulsewidth modulation (SPWM) inverter feeding five different chorded three-phase induction motors were tested up to first thirty harmonic voltage component at different loads. The results show that the artif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…As seen in many multidisciplinary studies that have done by the researchers [ [46] , [47] , [48] , [49] , [54] , [53] , [52] , [51] , [50] ], artificial neural networks have shown that they can be applied to any problem as a method that can solve complex problems inspired by biological nervous system easily, quickly and with scientific accuracy. The artificial neural network was trained with the data set of the study, the time of the operations of the production of emergency fixtures with 29 operations, the machine types, the priority order of the operations, the weight distributions of the operations and the efficiency values of each station.…”
Section: Materials and Methodologymentioning
confidence: 99%
“…As seen in many multidisciplinary studies that have done by the researchers [ [46] , [47] , [48] , [49] , [54] , [53] , [52] , [51] , [50] ], artificial neural networks have shown that they can be applied to any problem as a method that can solve complex problems inspired by biological nervous system easily, quickly and with scientific accuracy. The artificial neural network was trained with the data set of the study, the time of the operations of the production of emergency fixtures with 29 operations, the machine types, the priority order of the operations, the weight distributions of the operations and the efficiency values of each station.…”
Section: Materials and Methodologymentioning
confidence: 99%
“…It has been found that the optimal coil pitch can enhance the winding factor, which in turn enhances the fundamental induced voltage. In (Birbir & Nogay, 2007), harmonic analysis of the voltage and current has been performed for 1100W, 36-slot, three-phase, four-pole squirrel cage induction motors with full-pitch and different under-pitch configurations of the stator windings. The analysis has been carried out experimentally and the motors are supplied both using sinusoidal PWM inverter and sinusoidal voltage excitation.…”
Section: 𝐸 = √2𝜋𝑘 𝑤 𝑓𝑁 𝑝ℎ ømentioning
confidence: 99%
“…ANN is defined as a data processing system consisting of a large number of simple highly interconnected processing elements (artificial neuron) in architecture inspired by the structure of cerebral cortex of the brain [44]. Artificial Neural Networks (ANN) are an abstract simulation of a real nervous system that consists of a set of neural units connected to each other via axon connections which are very similar to the dendrites and the axons in biological nervous systems [45,46] Each layer employs several neurons and each neuron in a layer is connected to a neuron in the adjacent layer with different weights. With the exception of the input layer, each neuron receives signals from the neurons of the previous layer linearly weighted by the interconnect values between neurons.…”
Section: Artificial Neural Networkmentioning
confidence: 99%